Compiled service records of American naval personnel and members of the departments of the Quartermaster General and the Commissary General of Military Stores who served during the Revolutionary War (NARA, 1894)
Compiled service records consisting of a jacket-envelope for each soldier, sailor, or civilian, with holograph abstracts of entries relating to him found in original records. Compilation began in 1894, and the last major addition to the collection was made in 1914-1915.